Internet Addiction, Hikikomori Syndrome, and the Prodromal Phase of Psychosis - Stip, Emmanuel; Thibault, Alexis; Beauchamp-Chatel, Alexis; Kisely, Steve (Frontiers in Psychiatry, 2016)
Computers, video games and technological devices are part of young people's everyday lives. Hikikomori, a Japanese word describing a condition that mainly affects adolescents or young adults who live isolated from the world, cloistered within their parents’ homes, locked in their bedrooms for days, months or even years on end, refusing to communicate even with their family, using internet profusely and only venturing out to deal with their most imperative bodily needs. Although first described in Japan, cases have been described from around the world, this is the first published report from Canada. The disorder shares characteristics with prodromal psychosis, negative symptoms of schizophrenia or internet addiction, which are common differential or comorbid diagnoses. Certain cases, however, are not accompanied by a mental disorder. Psychotherapy is the treatment of choice although many cases are reluctant to present. The exact place of hikikomori in psychiatric nosology has yet to be determined. We searched Medline up to 12th May, 2015 supplemented by a hand search of the bibliographies of all retrieved articles. We used the following search terms: Hikikomori OR (prolonged AND social AND withdrawal). We found 97 potential papers. Of these 42, were in Japanese, and one in Korean. However, many of these were cited by subsequent English-language papers that were included in the review. Following scrutiny of the titles and abstracts, 29 were judged to be relevant. Further research is needed to distinguish between primary and secondary hikikomori and establish whether this is a new diagnostic entity, or particular cultural or societal manifestations of established diagnoses.